Study on interface thermodynamic mechanism of membrane fouling in flat sheet ceramic membrane treating oilfield produced water - Liu, Yiyang (Environmental technology, 2024)
In this study, a flat sheet ceramic membrane experimental device was constructed, and the thermodynamics of membrane fouling interface was studied for oilfield produced water. The flux of ceramic membrane in three kinds of model solutions were measured with time, as well as the surface tension, contact Angle and Zeta potential of solid. The thermodynamic mechanism of membrane fouling interface combined with XDLVO theory were explored for three kinds of model solutions. The thermodynamic study of the interface of ceramic plate membrane shows that the total interaction energy between membrane and oil droplets decreases with the increase of the distance between two interfaces at initial stage of membrane fouling, and finally transforms from the mutual attraction to the mutual repulsion. The total interaction energy between reservoir and oil droplet is shown as mutual attraction, and the total interaction energy decreases with the increase of the distance between reservoir and oil droplet interface. The zeta potential of crude oil was affected by salinity to some extent. The electrostatic shielding effect of the salt ions leads to a decrease in the ζ-potential of the three solutions. They are in the order: model solution A > model solution B > model solution C. This leads to a decrease in the electrostatic interaction (EL). And since the oil layer has the same composition as the oil droplets, the EL interactions in the three solutions can behave as mutual repulsion